Assessing Genetic Variability and Population Structure of Alnus glutinosa (Black Alder) in Kazakhstan Using SSR Markers - Aidana Nurtaza; Damira Dyussembekova; Alexandr Shevtsov; Symbat Islamova; Indira Samatova; Saule Koblanova; Olga Borodulina; Almagul Kakimzhanova (Plants)
Alnus glutinosa plays a crucial role in flood control, riverbank stabilization, and water purification. Recognized for its ecological significance, it is listed in the Red Book of Kazakhstan. This study investigated the genetic variability of A. glutinosa populations in Kazakhstan, analyzing 78 trees from seven populations in the Bayanaul mountain forest massif and the northern Turgay regions using 12 SSR markers. The study identified an average of 6.3 alleles and 2.783 effective alleles, as well as observed and expected heterozygosities of 0.570 and 0.562, respectively, reflecting genetic diversity. Among the populations, KS1 (northern Turgay) and PVL3 (Bayanaul) displayed the highest diversity, while PVL5 (Bayanaul) showed slightly lower diversity. The analysis of molecular variance results indicated that 86% of the genetic diversity occurred within populations, with 14% attributed to differences between populations. A UPGMA tree based on Nei’s genetic distance revealed three distinct clusters, suggesting geographically structured genetic variability in A. glutinosa populations.